PERADABAN ISLAM DI NUSANTARA PRA-KEMERDEKAAN DAN KONTRIBUSINYA TERHADAP PERKEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Muhammad Farras Afif Ibrahim Mamesah; Ahmad Saniyal Fikri; M. Yahya (CV. BAROKAH PUBLISHER, 2026)
This study examines the development of Islamic civilization in the Indonesian archipelago during the pre-independence period and its influence on the Islamic education system. Islamic civilization, which entered the Indonesian archipelago in the 7th century AD through trade routes, da'wah, and social interaction, developed peacefully by integrating Islamic values ​​into local culture through a process of acculturation. This process gave birth to Islamic kingdoms such as Samudera Pasai, Demak, Aceh Darussalam, Banten, and Islamic Mataram, as well as traditional institutions such as Islamic boarding schools (pesantren) in Java, surau (prayer houses) in Minangkabau, and dayah (Islamic boarding schools) in Aceh. The method used is qualitative research through library research with a historical-descriptive approach and triangulation of sources from various scientific journals and primary historical sources. The results of the study indicate that traditional Islamic educational institutions function not only as centers of religious learning, but also as a medium for the formation of moral character, social cohesion, and national awareness that would later become the foundation of the Indonesian independence struggle. Islamic civilization has been proven to make a significant contribution to the formation of the intellectual and social identity of pre-independence Indonesian society.